2020
DOI: 10.1002/jobm.202000407
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and repression of key rate‐limiting enzymes (acetyl CoA carboxylase and HMG reductase) to enhance fatty acid production from Rhodotorula mucilaginosa

Abstract: Implementing two‐way strategies to enhance the lipid production in Rhodotorula mucilaginosa with the help of metabolic engineering was focused on the overexpression of acetyl coenzyme A carboxylase (ACC1 carboxylase) gene and repression of 3‐hydroxy 3‐methylglutaryl reductase (HMG‐CoA reductase). Using an inducer (sodium citrate) and inhibitor (rosuvastatin), the amounts of biomass, lipid, and carotenoid were estimated. In the presence of inhibitor (200 mM), 62% higher lipid concentration was observed, while 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…4a). The similar discoloration was observed when rosuvastatin a chemical inhibitor was used for inhibition of HMG CoA reductase enzyme in previous work [5]. It observed that the biomass (banana peel) was better utilized in the chemical inhibited process as compared to the chemical inhibitor.…”
Section: Quality Of Fatty Acids Nutritionsupporting
confidence: 79%
See 2 more Smart Citations
“…4a). The similar discoloration was observed when rosuvastatin a chemical inhibitor was used for inhibition of HMG CoA reductase enzyme in previous work [5]. It observed that the biomass (banana peel) was better utilized in the chemical inhibited process as compared to the chemical inhibitor.…”
Section: Quality Of Fatty Acids Nutritionsupporting
confidence: 79%
“…In our previous work, it was reported the chemical inhibitor like NaCl and ionic liquid in isolation or combination were shifted the ux towards the accumulation of a higher percentage of SFA in a yeast cell. This SFA may be provided better protection from cell membrane osmosis [5]. In reverse, the natural inhibitor encouraged yeast for the production of UFA, which may be in uenced by the phytomolecules of P. cineraria aqueous extract.…”
Section: Quality Of Fatty Acids Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinatorial regulation is a beneficial modification strategy that simultaneously targets multiple metabolic nodes and has been successfully applied in other microorganisms ( Li et al, 2012 ; Chaturvedi et al, 2021 ). When metabolic regulators are combined in the fermentation process, multiple nodes of the synthesis process can be simultaneously regulated to increase the regulation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Several biotin-containing enzyme systems were identifiable via sequence homology, which could generate the malonyl-CoA substrate that is used by FAS to elongate the fatty acid. These enzymes carboxylate acyl-CoA substrates, including acetyl-CoA, and thereby generate malonyl-CoA ( Nikolau et al, 2003 ), which is considered to be the rate-limiting reaction for fatty acid biosynthesis ( Davis et al, 2000 ; Chaturvedi et al, 2021 ). Prior experimental characterization has identified one of these biotin-containing enzymes as being capable of carboxylating acetyl-CoA, propionyl-CoA, or butyryl-CoA ( Shivaiah et al, 2021 ), but whether T. fusca encodes other proteins that can also carboxylate acetyl-CoA will require similar characterizations.…”
Section: Discussionmentioning
confidence: 99%